Kepuasan Masyarakat terhadap Pelayanan Publik Bidang Pendidikan(Penelitian Survei pada Zona Wilayah Koordinasi Layanan Administrasi Satuan Pendidikan di Kabupaten Pandeglang) - Sutoto Sutoto (LPPM STIA Banten, 2022)
Publicservice in education held at the district, sub-district and education unit levels are seen as slow, long and unsatisfactory. Several actual issues were identified, including: (1) unclear service time; (2) the practice of illegal levies; and (3) unfriendlybehavior of employees. The research was conducted using survey, observation and interview methods by taking samples divided into 6 (six) zones for the coordination of administrative services of the education unit. From the results of the study it was concluded that the services at the Education Office, State Elementary Schools and State Junior High Schools were considered quite satisfied. As many as 71.6 percent of respondents answered quite satisfied, while respondents who stated that they were not satisfied were 13.2 percent. The remaining 15.2 percent answered they did not know